Odpowiedzi

Najlepsza Odpowiedź!
2009-12-07T19:23:28+01:00
1) 5(3-x)+x-3/2=3x+5
15 - 5x +x - 3/2 = 3x + 5
- 7x = - 24/2 /*2
- 14x = 24
x = 1 5/7

3) 4(x-1)+2x-1\3 =3x-1
4x - 4 + 2x - 1/3 = 3x -1
3x = 10/3 /*3
9x = 10
x = 1 1/9

5) 5-x\2-2(2x+5)=2x-1
5 - x/2 - 4x - 10 = 2x - 1
- x/2 - 6x = 4
-x - 12x = 8
- 13x = 8
x = - 1 5/8

7) x-1\3+5(x+3)=2-x
x - 1/3 + 5x + 15 = 2 - x
7 x = -38/3
28x = - 38
x = - 1 5/14
2 5 2
2009-12-07T19:29:12+01:00
1) 5(3-x)+x-3/2=3x+5
15 - 5x +x - 3/2 = 3x + 5
- 7x = - 24/2 /*2
- 14x = 24
x = 1 5/7

3) 4(x-1)+2x-1\3 =3x-1
4x - 4 + 2x - 1/3 = 3x -1
3x = 10/3 /*3
9x = 10
x = 1 1/9

5) 5-x\2-2(2x+5)=2x-1
5 - x/2 - 4x - 10 = 2x - 1
- x/2 - 6x = 4
-x - 12x = 8
- 13x = 8
x = - 1 5/8

7) x-1\3+5(x+3)=2-x
x - 1/3 + 5x + 15 = 2 - x
7 x = -38/3
28x = - 38
x = - 1 5/14